SAT0143 A PHASE 1 STUDY IN HEALTHY VOLUNTEERS EXPLORING THE SAFETY, PHARMACOKINETICS AND PHARMACODYNAMICS OF ATI-450: A NOVEL ORAL MK2 INHIBITOR. (13th June 2020) - Schnyder, J.; Monahan, J.; Smith, W.; Hope, H.; Kelly, D.; Burt, D.; Huff, E.; Kaul, A.; Hildebrand, A.; Burnette, B.; Klug, N.; Bangs, M.; et al.
Abstract : Background: ATI-450, is an investigational small molecule inhibitor of the MAPK-activated protein kinase 2 (MK2) signaling pathway. This pathway drives the expression of multiple cytokines including TNFα, IL-1α and β, and IL-6. Objectives: We evaluated the safety and tolerability of ATI-450 in healthy volunteers as well as pharmacokinetics (PK) and pharmacodynamics (PD). Here we present data from single and multiple ascending dose cohorts. The aim was to select a dose for evaluation in phase 2 in patients with rheumatoid arthritis. Methods: Safety, PK and PD were assessed in a randomized, observer-blind, placebo-controlled, phase 1 study in male and female healthy subjects aged 18-55 (n=77). Part A: Single Ascending Dose (SAD) (n=32, 8 subjects per dose cohort - 2 placebo, 6 active). A single dose of 10mg, 30mg, 50mg and 100mg was tested. Part B: Multiple Ascending Dose (MAD) (n=30, 10 subjects per dose cohort - 2 placebo, 8 active). 10mg BID, 30mg BID and 50mg BID doses were tested over 7 days of administration. Safety and tolerability of ATI-450 was evaluated based on adverse events, clinical laboratory, vital signs, 12-lead ECG, Holter monitoring, and physical examination. Blood was drawn for PK analysis at 0.5, 1, 2, 4, 6, 8, 12 hours, 24, 36, and 48 hours post dose in the SAD cohort and on day 7 of the MAD cohort. PD of ATI-450 were explored by investigating the inhibition of a target biomarker, phospho-HSP27 (pHSP27) and proinflammatory cytokines, TNFα, IL1β, IL6 and IL8 in ex-vivo LPS-stimulated blood samples collected 4 and 12 hours post dose on day 7 from subjects in the MAD cohorts. Results: ATI-450 was generally well tolerated. No serious adverse events or severe adverse events were reported, and no adverse events led to discontinuation of the study medication. The most common adverse events (reported by 2 or more subjects who received ATI-450) observed during the trial were dizziness, headache, upper respiratory tract infection, constipation, nausea, and abdominal pain. All adverse events were mild. A trend of a decrease in absolute neutrophil count (ANC) was observed without correlated clinical sequelae. ATI-450 had dose proportional PK with a terminal half-life (t½) of 9-12 hours in the MAD cohort on day 7. A dose and concentration dependent inhibition of ex vivo stimulated cytokines and target biomarker was observed. On day 7, patients in the 50mg BID dose (the dose with the highest degree of inhibition) recorded mean trough drug levels (12 hours post dose) that were 1.4, 2.5, 2.5 and 2.4 times greater than the IC80 for TNFα, IL1β, IL8 and pHSP27 respectively. Mean Cmax drug levels (4 hours post dose) were 3.6, 6.4, 6.2 and 6.0 times greater than the IC80 for TNFα, IL1β, IL8 and pHSP27 respectively. IL6 levels were inhibited by more than 50% for part of the dosing interval. Conclusion: Oral ATI-450 was generally well tolerated at all doses with dose proportional PK. The t½ suggests that once or twice daily oral dosing may be possible. At the 50mg BID dose, marked inhibition of TNFα, IL1β and IL8, IL6 and pHSP27 was observed. ATI-450 has the potential to be an oral, small molecule drug which can target multiple cytokines. Exploration of its benefit to risk profile in patients with rheumatoid arthritis is warranted. Disclosure of Interests: Judy Schnyder Shareholder of: aclaris therapeutics, Employee of: aclaris therapeutics, Joe Monahan Shareholder of: aclaris therapeutics, Employee of: aclaris therapeutics, Walter Smith Shareholder of: aclaris therapeutics, Employee of: aclaris therapeutics, Heidi Hope Shareholder of: aclaris therapeutics, Employee of: aclaris therapeutics, Deborah Kelly Shareholder of: aclaris therapeutics, Employee of: aclaris therapeutics, David Burt Shareholder of: aclaris therapeutics, Employee of: aclaris therapeutics, E Huff Shareholder of: aclaris therapeutics, Employee of: aclaris therapeutics, A Kaul Shareholder of: aclaris therapeutics, Employee of: aclaris therapeutics, A Hildebrand Shareholder of: aclaris therapeutics, Employee of: aclaris therapeutics, B Burnette Shareholder of: aclaris therapeutics, Employee of: aclaris therapeutics, N Klug Shareholder of: aclaris therapeutics, Employee of: aclaris therapeutics, M Bangs Shareholder of: Aclaris Therapeutics, Employee of: Aclaris Therapeutics, David Gordon Shareholder of: aclaris therapeutics, Employee of: aclaris therapeutics